2019
DOI: 10.1021/acs.est.9b05362
|View full text |Cite
|
Sign up to set email alerts
|

Significant Underestimation of Gaseous Methanesulfonic Acid (MSA) over Southern Ocean

Abstract: Methanesulfonic acid (MSA), derived from the oxidation of dimethylsulfide (DMS), has a significant impact on biogenic sulfur cycle and climate. Gaseous MSA (MSA g ) has been often ignored in previous studies due to its quick conversion to particulate MSA (MSA p ) and low concentrations. MSA g , MSA p , and nss-SO 4 2− were observed simultaneously for the first time with high-timeresolution (1 h) in the Southern Ocean (SO). The mean MSA g level reached up to 3.3 ± 1.6 pptv, ranging from ∼24.5 pptv in the SO, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…Graf et al (1997) reported that the marine DMS emissions made up 25% of the global nss‐SO 4 2− burden. The ratio of methanesulfonic acid to nss‐SO 4 2− can be used as a tracer for marine biogenic nss‐SO 4 2− to indicate the relative contributions of biogenic and anthropogenic sources to the sulfate budget (Choi et al 2017; Yan et al 2019), with higher ratios indicating that a larger fraction is derived from the oxidation of DMS. The average ratio of methanesulfonic acid to nss‐SO 4 2− in this study was 2.4% (0.3%–5.3%), which agreed with the survey results of Jung et al (2014) and Wang et al (2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graf et al (1997) reported that the marine DMS emissions made up 25% of the global nss‐SO 4 2− burden. The ratio of methanesulfonic acid to nss‐SO 4 2− can be used as a tracer for marine biogenic nss‐SO 4 2− to indicate the relative contributions of biogenic and anthropogenic sources to the sulfate budget (Choi et al 2017; Yan et al 2019), with higher ratios indicating that a larger fraction is derived from the oxidation of DMS. The average ratio of methanesulfonic acid to nss‐SO 4 2− in this study was 2.4% (0.3%–5.3%), which agreed with the survey results of Jung et al (2014) and Wang et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…index.php), the nss-SO 4 2À at P1 was also replenished by an anthropogenic source. Graf et al (1997) (Choi et al 2017;Yan et al 2019), with higher ratios indicating that a larger fraction is derived from the oxidation of DMS. The average ratio of methanesulfonic acid to nss-SO 4 2À in this study was 2.4% (0.3%-5.3%), which agreed with the survey results of Jung et al (2014) and Wang et al (2019).…”
Section: Contribution Of Biogenic Source To Atmospheric Sulfate Aerosolsmentioning
confidence: 99%
“…Chen et al, 2018;Hoffmann et al, 2016) and increases the mass of aerosols activated in cloud droplets (cloud processing). MSA constitutes a large fraction of the secondary aerosol mass over the Southern Ocean, up to 𝐴𝐴 50% compared to the non-sea-salt sulphate aerosol mass (Preunkert et al, 2007;Yan et al, 2019), but its contribution to the CCN budget has not been quantified so far.…”
mentioning
confidence: 99%
“…Our simulation shows that the gas-phase MSA formation is small compared to aqueous-phase formation, in line with previous work (Barnes et al, 2006;von Glasow and Crutzen, 2004;Zhu et al, 2006;Hoffmann et al, 2016;Chen et al, 2018;Hoffmann et al, 2021). Near the sea surface, simulated gas-phase MSA is < 0.03 ppt even in Southern Hemisphere summer, while a recent ship-based measurement reported an averaged concentration ranged 1.4-25 ppt (Yan et al, 2019). The model also substantially underestimates gas-phase MSA (<0.001 ppt) when compared to a wintertime site measurements in Germany (0.5-10 ppt) (Stieger et al, 2021).…”
Section: Comparison With Observationsmentioning
confidence: 70%
“…As discussed in Sect. 3.2, it is likely that our model overestimates the concentration of particulate MSA and underestimate gaseous MSA when compared with in situ measurements (e.g., ATom, and Yan et al (2019) in the Southern Ocean. This could result in an overestimate of sulfate given that gas-phase MSA is expected to have a longer lifetime than particulate MSA and H2SO4 vapor (Berresheim, 2002).Our comparisons with observations also suggest that emissions of DMS, in particular a likely overestimate over the Southern Ocean, play an important role in dictating the regional loading of secondary oxidation products This study included a relatively new chemical mechanism for the formation and loss of HPMTF.…”
Section: Discussionmentioning
confidence: 84%